(untitled) (Social Science Review, 2025)
The contemporary world stage is marked by profound discord and conflict among global leaders, driven by stark ideological disparities and elusive national interests. This paper contends that these prevailing conditions render the pursuit of global peace a formidable and intricate endeavour within the framework of existing global governance. The central argument of this paper underscores the imperative for a humane global governance paradigm to achieve global peace and security. Findings reveal that multilateral diplomacy, characterized by its inclusiveness, must serve as a potent tool for strengthening international organizations and global governance. Consequently, it will nurture the development of agreements within a rule-based framework, enabling us to effectively confront the issues raised by nationalism and populism. This, in the end, contributes to solidifying backing for initiatives promoting global governance. In doing so, it adopts a methodological approach that draws on pertinent literature, individual perspectives, academic publications, and selected journal articles that bear relevance to these matters. Social Science Review, Vol. 41(1), June 2024, Page 145-160.